2020
DOI: 10.1088/1742-6596/1693/1/012161
|View full text |Cite
|
Sign up to set email alerts
|

A Military Named Entity Recognition Method based on pre-training language model and BiLSTM-CRF

Abstract: Military named entity recognition is the basis of the military intelligence analysis and operational information service. In order to solve the problems of inaccurate word segmentation, diverse forms and the lack of corpus in military texts, the author proposes a method of military named entity recognition based on Pre-training language model. On this basis, and taking advantage of Bi-directional Long Short-Term Memory (BiLSTM) neural network in dealing with the wide range of contextual information, the BERT-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The emergence of question and answer (Q&A) systems presents an opportunity to overcome this issue. Named entity recognition (NER) is now widely used in the military ( Wang et al., 2018 ; Lu et al., 2020 ; Baigang and Yi, 2023 ; Li et al., 2023 ), entertainment and culture ( Molina-Villegas et al., 2021 ; Zhuang et al., 2021 ; Fu et al., 2022 ; Huang et al., 2022 ), cybersecurity ( Georgescu et al., 2019 ; Simran et al., 2020 ; Chen et al., 2021 ; Ma et al., 2021 ), and medicine ( Ji et al., 2019 ; Li et al., 2020 ; Wang et al., 2020 ; Liu et al., 2022 ). However, the application of NER in the agricultural sector is still in the early stages of development ( Wang et al., 2022 ; Yu et al., 2022a ; Qian et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of question and answer (Q&A) systems presents an opportunity to overcome this issue. Named entity recognition (NER) is now widely used in the military ( Wang et al., 2018 ; Lu et al., 2020 ; Baigang and Yi, 2023 ; Li et al., 2023 ), entertainment and culture ( Molina-Villegas et al., 2021 ; Zhuang et al., 2021 ; Fu et al., 2022 ; Huang et al., 2022 ), cybersecurity ( Georgescu et al., 2019 ; Simran et al., 2020 ; Chen et al., 2021 ; Ma et al., 2021 ), and medicine ( Ji et al., 2019 ; Li et al., 2020 ; Wang et al., 2020 ; Liu et al., 2022 ). However, the application of NER in the agricultural sector is still in the early stages of development ( Wang et al., 2022 ; Yu et al., 2022a ; Qian et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Military entity recognition technology is based on general entity recognition technology, which has experienced the development process from dictionary, rule, and machine learning to deep learning [3]. At present, the recognition model based on pretraining language model and deep learning algorithm is the main stream of entity recognition in military and general fields with the increasing computing power of small computers, the maturity of deep learning technology, and the development of pretraining language model [4]. However, it is a challenge work for the military entity recognition with the distinct domain characteristics of military field.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al (2020) [5] put forward an attention-based multi-task NN (Neural Network) text classification and sequence labeling model and applied it to the NER and intention analysis of Chinese online medical problems. Lu et al (2020) [6] projected a military NER method based on a pre-training language model. Experimental results on labeled military text corpus showed that the proposed method outperformed the traditional method.…”
Section: Introductionmentioning
confidence: 99%